Safety and immunogenicity of co-administration of meningococcal type A and measles–rubella vaccines with typhoid conjugate vaccine in children aged 15–23 months in Burkina Faso. (January 2021) - Sirima, Sodiomon B.; Ouedraogo, Alphonse; Barry, Nouhoun; Siribie, Mohamadou; Tiono, Alfred B.; Nébié, Issa; Konaté, Amadou T.; Berges, Gloria Damoaliga; Diarra, Amidou; Ouedraogo, Moussa; Soulama, Issiaka; Hema, Alimatou; et al.
Highlights: This is the first study on the co-administration of typhoid conjugate vaccine (TCV) in West Africa. Co-administration of TCV with routine vaccines in a typhoid-endemic country was successful. TCV was safely co-administered at 15 months with group A meningococcal conjugate vaccine. Single-dose TCV was immunogenic in 15-month-old children. There was no safety signal related to TCV vaccination or co-administration. Abstract: Objectives: The World Health Organization pre-qualified single-dose typhoid conjugate vaccine (TCV) and requested data on co-administration with routine vaccines. The co-administration of Typbar TCV (Bharat Biotech International) with routine group A meningococcal conjugate vaccine (MCV-A) and measles–rubella (MR) vaccine was tested. Methods: This was a double-blind, randomized controlled trial performed in Ouagadougou, Burkina Faso. Children were recruited at the 15-month vaccination visit and were assigned randomly (1:1:1) to three groups. Group 1 children received TCV plus control vaccine (inactivated polio vaccine) and MCV-A 28 days later; group 2 children received TCV and MCV-A; group 3 children received MCV-A and control vaccine. Routine MR vaccine was administered to all participants. Safety was assessed at 0, 3, and 7 days after immunization, and unsolicited adverse events and serious adverse events were assessed for 28 days and 6 months after immunization, respectively. Results: A total of 150 children were recruited and vaccinated. Solicited symptoms were infrequent and similar for TCV and control recipients, as were adverse events (group 1, 61.2%; group 2, 64.0%; group 3, 68.6%) and serious adverse events (group 1, 2.0%; group 2, 8.0%; group 3, 5.9%). TCV generated robust immunity without interference with MCV-A vaccine. Conclusions: TCV can be safely co-administered at 15 months with MCV-A without interference. This novel study on the co-administration of TCV with MCV-A provides data to support large-scale uptake in sub-Saharan Africa.